Southern grit : 100+ down-home recipes for the modern cook - Clark, Kelsey Barnard (Chronicle Books, 2021)
"A modern take on Southern cooking with 100 accessible recipes and lifestyle tips, from 2016 Top Chef winner and fan favorite Kelsey Barnard Clark"--